2020
DOI: 10.4025/actasciagron.v43i1.45189
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-phenological and agronomic performance of strawberry cultivars with different photoperiodic flowering responses

Abstract: The adaptability of the strawberry is known; however, little is known about the morphological and agronomic performance of these runner plants when transplanted in the Southern Hemisphere. The objective of this study was to evaluate whether strawberry cultivars classified according to their flowering differ in morpho-phenology and agronomic performance. Six cultivars of strawberry were used, two of which were Short Day (SD), Camarosa and Camino Real, and four of which were Neutral Day (ND), Aromas, Albion, Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The recommendation of Camarosa instead of Albion would provide undesired values for productive traits such as higher number and weight of non-commercial fruits, phenological traits such as higher period to the beginning of the harvest, and qualitative traits such as lower values of total soluble solids and esh rmness. Previous studies have also shown that the beginning of owering is similar for Camarosa and Albion, but full owering is achieved early in Albion (Castoldi da Costa et al, 2020). This results in the late beginning of harvest for Camarosa compared to Albion ( Supplementary Fig.…”
Section: T1mentioning
confidence: 76%
See 1 more Smart Citation
“…The recommendation of Camarosa instead of Albion would provide undesired values for productive traits such as higher number and weight of non-commercial fruits, phenological traits such as higher period to the beginning of the harvest, and qualitative traits such as lower values of total soluble solids and esh rmness. Previous studies have also shown that the beginning of owering is similar for Camarosa and Albion, but full owering is achieved early in Albion (Castoldi da Costa et al, 2020). This results in the late beginning of harvest for Camarosa compared to Albion ( Supplementary Fig.…”
Section: T1mentioning
confidence: 76%
“…Considering a univariate recommendation based on fruit yield solely, Camarosa cultivar would be recommended instead Albion since, on average, it is more productive ( Supplementary Fig S16A). Previous studies also reported the high total fresh fruit mass of Camarosa compared to Albion (Castoldi da Costa et al, 2020). This is explained mainly because Camarosa can increase the emission of crowns compared to Albion, resulting in a higher number of leaves.…”
Section: T1mentioning
confidence: 83%
“…The recommendation of Camarosa with transplants of National origin based on FY would result in higher fruit production. Previous studies also reported a greater total fresh fruit mass of Camarosa compared to Albion [ 49 ]. This is explained mainly because Camarosa can increase the emission of crowns compared to Albion, resulting in a higher number of leaves.…”
Section: Discussionmentioning
confidence: 72%
“…1.4). Previous studies have also shown that the beginning of flowering is similar for Camarosa and Albion, but full flowering is achieved later in the Albion cultivar [ 49 ]; this characteristic may be undesired by growers.…”
Section: Discussionmentioning
confidence: 99%
“…The extended photoperiod is one of the methods that reduce the duration of the plant cycles [ 23 , 24 ]. In many studies, it has been demonstrated that extended photoperiod have a positive benefit effect for breeding, by accelerating flowering and reducing plant life cycle in Safflower [ 25 ], Strawberry [ 26 ], Soybean [ 27 ], Barley [ 28 ], Wheat [ 29 ], Chickpea [ 30 ], Faba-Bean [ 31 ] and Lentil [ 23 , 32 , 33 ]. The extended photoperiod can be achieved with artificial light [ 34 ].…”
Section: Introductionmentioning
confidence: 99%